2018
DOI: 10.1038/s41396-017-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple colonist pools shape fiddler crab-associated bacterial communities

Abstract: Colonization is a key component of community assembly because it continuously contributes new species that can potentially establish and adds individuals to established populations in local communities. Colonization is determined by the regional species pool, which is typically viewed as stable at ecological time scales. Yet, many natural communities including plants, birds and microbes, are exposed to several distinct and dynamic sources of colonists and how multiple colonist pools interact to shape local com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 109 publications
(123 reference statements)
3
27
1
Order By: Relevance
“…High similarity in species composition between a local community and a colonist pool reflects strong influence of immigration from that specific source, and thus reveals the main colonist pool. In a previous study, comparing bacterial communities from fiddler crabs and sediment revealed that surface and burrow sediment bacteria colonize fiddler crab carapaces and guts (Cuellar‐Gempeler and Leibold ). These results coincide with the fiddler crab natural history because these crabs feed on organic matter, microalgae, and bacteria by scraping the surface sediment (Dye and Lasiak ), and build J‐shaped burrows to escape from predation and extreme temperatures (Kristensen ).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…High similarity in species composition between a local community and a colonist pool reflects strong influence of immigration from that specific source, and thus reveals the main colonist pool. In a previous study, comparing bacterial communities from fiddler crabs and sediment revealed that surface and burrow sediment bacteria colonize fiddler crab carapaces and guts (Cuellar‐Gempeler and Leibold ). These results coincide with the fiddler crab natural history because these crabs feed on organic matter, microalgae, and bacteria by scraping the surface sediment (Dye and Lasiak ), and build J‐shaped burrows to escape from predation and extreme temperatures (Kristensen ).…”
Section: Introductionmentioning
confidence: 94%
“…We expect burrow sediment to represent the main colonist pool for carapace bacterial communities, whereas surface sediment might contribute fewer, but possibly important key colonists. Based on previous findings (Cuellar‐Gempeler and Leibold ), we expect the gut to receive a mix of colonists from the surface and burrow sediments. However, we expect that strong habitat filters imposed by oral apparatus and hepatopancreas secretions (Vogt et al.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations